2014
DOI: 10.3109/13561820.2014.939744
|View full text |Cite
|
Sign up to set email alerts
|

Using realist synthesis to understand the mechanisms of interprofessional teamwork in health and social care

Abstract: Realist synthesis offers a novel and innovative way to interrogate the large literature on interprofessional teamwork in health and social care teams. This article introduces realist synthesis and its approach to identifying and testing the underpinning processes (or "mechanisms") that make an intervention work, the contexts that trigger those mechanisms and their subsequent outcomes. A realist synthesis of the evidence on interprofessional teamwork is described. Thirteen mechanisms were identified in the synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 26 publications
2
60
0
6
Order By: Relevance
“…This article completes a series of four articles (Hewitt, Sims, & Harris, 2014 that report on a realist synthesis of interprofessional teamworking addressing the question: ''through what mechanisms does teamworking affect outcomes and experience (patient, carer, staff and service) and how does context influence those mechanisms and outcomes?'' This synthesis was conducted as part of a wider study exploring the impact of interprofessional teamworking on patient and carer experience and outcomes after stroke (Harris et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This article completes a series of four articles (Hewitt, Sims, & Harris, 2014 that report on a realist synthesis of interprofessional teamworking addressing the question: ''through what mechanisms does teamworking affect outcomes and experience (patient, carer, staff and service) and how does context influence those mechanisms and outcomes?'' This synthesis was conducted as part of a wider study exploring the impact of interprofessional teamworking on patient and carer experience and outcomes after stroke (Harris et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Das heute bestehende Konzept der Gesundheitsfakultät Linköping wurde von dem im OECD-Prozess involvierten Rektor Areskog vorangetrieben und 1986 von den nationalen Gremien genehmigt (Areskog, 1981(Areskog, , 1992 (Hylin, 2010, S. 11-13). Berlin et al, 2013;Hylin, 2010;Reeves et al, 2013;Hewitt et al, 2014. (Nordenström et al, 2013;Regeringskansliet, 2010;Berlin et al, 2013).…”
Section: Linköping Ursprünge Des Pioniermodells Von Linköpingunclassified
“…The development of trust and respect among team members is thought to be one key relational factor central to successful interprofessional teams [1]. Using realist synthesis of multiple interprofessional studies, Hewitt, Sims & Harris [17] also identified "support and value" as one of the key mechanisms for interprofessional teamwork. Particularly when psychologists are often "late to the party" in terms of joining already established medical teams, some of which may already have psychosocial providers involved such as social work, it is critical that they get to know the culture of the team and contribute to a mutually respectful working environment.…”
Section: Facilitators Of Interprofessional Teamworkmentioning
confidence: 99%